2016
DOI: 10.1111/omi.12165
|View full text |Cite
|
Sign up to set email alerts
|

Global TLR2 and 4 deficiency in mice impacts bone resorption, inflammatory markers and atherosclerosis to polymicrobial infection

Abstract: SUMMARY oll-like-receptors (TLRs) play a significant role in the generation of a specific innate immune response against invading pathogens. TLR2 and TLR4 signaling contributes to infection-induced inflammation in periodontal disease (PD) and atherosclerosis. Increased observational studies points towards a relationship between PD and atherosclerosis, but the role of TLR2 and TLR4 in recognition of multiple oral pathogens and their modulation of host response leading to atherosclerosis are not clear. We evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 54 publications
2
45
0
Order By: Relevance
“…Interestingly, the dysregulated recruitment of neutrophils into the JE and alteration in microbial composition of these TLR KO mice did not affect alveolar bone levels. This result is consistent with previous observations in a mouse model, which found no significant differences in alveolar bone loss between uninfected control TLR2 and TLR4 KO mice and also in a rabbit model of disease investigating the contribution of periopathogens to initiate dysbiosis in oral communities, which showed that not all dysbiotic communities induced bone loss . This suggests that periodontitis is a complex disease process that requires more than a dysbiotic microbial community and may require engagement of additional components yet to be elucidated.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, the dysregulated recruitment of neutrophils into the JE and alteration in microbial composition of these TLR KO mice did not affect alveolar bone levels. This result is consistent with previous observations in a mouse model, which found no significant differences in alveolar bone loss between uninfected control TLR2 and TLR4 KO mice and also in a rabbit model of disease investigating the contribution of periopathogens to initiate dysbiosis in oral communities, which showed that not all dysbiotic communities induced bone loss . This suggests that periodontitis is a complex disease process that requires more than a dysbiotic microbial community and may require engagement of additional components yet to be elucidated.…”
Section: Discussionsupporting
confidence: 92%
“…Alternatively, the absence of TLR2 or TLR4 may indicate a critical role for these TLRs in limiting excessive neutrophil infiltration to sites of infection via dampening chemokine receptor expression or functions. Lending support to this possibility, ex vivo experiments in human neutrophils and in vivo experiments in mouse models demonstrated that TLR2 and TLR4 activation downregulates the cell surface expression of CXCR2 on neutrophils, impairing chemotaxis. Furthermore, it was observed that deficiency of TLR2 prevented CXCR2 downregulation and relieved impairment of neutrophil numbers in lung tissue in a mouse model of sepsis .…”
Section: Discussionmentioning
confidence: 96%
“…Recently they also discovered that in TLR2 −/− TLR4 −/− mice infected with polymicrobial infection including P. gingivalis, T. denticola, T. forsythia, and F. nucleatum, atherosclerotic plaque progression was significantly reduced. However, bacterial genomic DNA was detected in multiple organs indicating an intravascular dissemination from gingival tissue to heart, aorta, kidney and lungs, suggesting that TLR2 and 4 were dispensable for systemic spread after polybacterial infections but TLR2 and 4 deficiency markedly reduces atherosclerosis induced by oral bacteria [96]. These results illustrated the role of TLR2 and 4 in atherosclerosis of periodontal bacterial infection, suggesting that focusing on periodontal disease may furnish new therapeutic options for the treatment of patients with atherosclerosis.…”
Section: Periodontal Pathogensmentioning
confidence: 86%
“…Indeed, organisms such as Fusobacterium nucleatum and others have demonstrated capacity drive inflammation in a manner that involves TLR signaling [ 96 , 97 , 98 ]. In addition to single organisms, others have shown that polymicrobial challenge evoke strong oral bone loss activities [ 99 ], and can negatively influence systemic diseases such as atherosclerosis [ 100 ]. Thus, in our attempt to focus the review, it is important to note that other oral organisms may display important attributes that lead to similar outcomes as those that we highlight herein for P. gingivalis .…”
Section: Periodontal Diseases and Toll-like Receptorsmentioning
confidence: 99%